Environmental factors associated With Toxoplasma gondii Exposure in Neotropical Primates of Costa Rica - Niehaus, Carmen; Spínola, Manuel; Su, Chunlei; Rojas, Norman; Rico-Chávez, Oscar; Ibarra-Cerdeña, Carlos N.; Foley, Janet; Suzán, Gerardo; Gutiérrez-Espeleta, Gustavo A.; Chaves, Andrea (Frontiers in Veterinary Science, 2020)
The apicomplexan parasite Toxoplasma gondii (T. gondii) has been found in more than 350 species of homoeothermic vertebrates in diverse climates and geographic areas. In most animals, T. gondii produces mild or asymptomatic infection. However, acute and hyperacute toxoplasmosis is associated with high mortality rates observed in Neotropical primates (NP) in captivity. NP are distributed in 20 countries across the Americas, and although infection has been reported in certain countries and species, toxoplasmosis in the wild and its impact on NP population survival is unknown. Differences among species in exposure rates and disease susceptibility may be due in part to differences in host behavior and ecology. Four species of NP are found in Costa Rica, i.e. howler (Alouatta palliata), spider (Ateles geoffroyi), capuchin (Cebus imitator), and squirrel monkeys (Saimiri oerstedii). This study reports NP exposure to T. gondii using the modified agglutination test (MAT) in 245 serum samples of NP (198 wild and 47 from captivity) from Costa Rica. Associations of serostatus with environmental (forest cover, annual mean temperature), anthropogenic (human population density), and biological (sex) variables in howler and capuchin monkeys were evaluated. The seroprevalence among wild NP was 11.6% (95% CI = 7.7-17.34), compared with 60% in captive monkeys (95% CI = 44.27-73.63), with significant differences between species (P value <0.05), suggesting an effect of behavior and ecology. In general, antibody titers were low for wild NP (<1:128) and high for captive NP (>1:8192), suggesting higher exposure due to management factors and increased life span in captivity. Seropositivity in howler monkeys was positively related to forest cover and inversely related to annual rainfall. For capuchins, annual rainfall was inversely related to seropositivity. Surveillance of T. gondii exposure in NP in captivity and in the wild is required to understand drivers of the infection and develop novel strategies to protect them.